2020
DOI: 10.1002/jaba.763
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cultural adaptations in the global application of ABA‐based telehealth services

Abstract: With telehealth gaining acceptance as a service delivery method, behavior analysts are now providing services to individuals worldwide. This review highlights the cultural adaptations used in ABA-based telehealth treatments for individuals with ASD outside of the United States. Nine studies met our inclusion criteria and the data were synthesized narratively. All studies reported some type of cultural adaptation, with most studies reporting changes made to the service delivery method. This included using trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 48 publications
2
20
0
1
Order By: Relevance
“…We also found that men who used a firearm for suicide tended to be over-represented in the less-diagnosed class. This is consistent with past findings [14] and may reflect that firearm suicide deaths may be characterized by a greater degree of impulsivity [20]. Because firearms are the most lethal means of inflicting self-injury [21], a person who impulsively attempts suicide with a firearm is much more likely to die as a result of the attempt than if they had made the attempt using any other method.…”
Section: Sexsupporting
confidence: 91%
“…We also found that men who used a firearm for suicide tended to be over-represented in the less-diagnosed class. This is consistent with past findings [14] and may reflect that firearm suicide deaths may be characterized by a greater degree of impulsivity [20]. Because firearms are the most lethal means of inflicting self-injury [21], a person who impulsively attempts suicide with a firearm is much more likely to die as a result of the attempt than if they had made the attempt using any other method.…”
Section: Sexsupporting
confidence: 91%
“…Whilst these US-based international studies are vital and welcomed additions to the literature, there is a dearth of research being produced by global researchers (i.e., studies in which neither researcher nor participants are located within the US). This has been highlighted in a recent review (Sivaraman & Fahmie, 2020 ). Emerging research, although limited, has indicted international replications are possible (e.g., Craig et al 2021 ) but to date and to the best of our knowledge there have been no studies published by researchers outside of the US investigating solely a telehealth platform to provide training to parents in naturalistic interventions.…”
mentioning
confidence: 86%
“…The cultural appropriateness and acceptability of telehealth consultations and development of cultural frameworks to guide telehealth use should be considered more broadly, particularly if services are being delivered transnationally. 69 , 70 …”
Section: Discussionmentioning
confidence: 99%